2022
DOI: 10.1016/j.vaccine.2022.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Phase I interim results of a phase I/II study of the IgG-Fc fusion COVID-19 subunit vaccine, AKS-452

Abstract: To address the coronavirus disease 2019 (COVID-19) pandemic caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a recombinant subunit vaccine, AKS-452, is being developed comprising an Fc fusion protein of the SARS-CoV-2 viral spike protein receptor binding domain (SP/RBD) antigen and human IgG1 Fc emulsified in the water-in-oil adjuvant, Montanide™ ISA 720. A single-center, open-label, phase I dose-finding and safety study was conducted with 60 healthy adults (18–65 years) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…A possible limitation of these hamster studies is that, as shown previously, RBD-based vaccines may be less immunogenic in hamsters, for reasons that are unclear 39 . This limitation does not apply to humans where RBD-based vaccines are effective 8,40,41 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible limitation of these hamster studies is that, as shown previously, RBD-based vaccines may be less immunogenic in hamsters, for reasons that are unclear 39 . This limitation does not apply to humans where RBD-based vaccines are effective 8,40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…While the vaccine has been extensively tested in mice, including mouse and human Fc versions, as well as rats and hamsters, we await the results of clinical trials to determine how immunogenic our vaccine is in humans. Based on results from phase I/II clinical trials of other experimental ancestral strain RBD-Fc protein vaccines used in prime-boost regimen in humans, albeit with different adjuvants 40, 41, 51 , and our preclinical data, we anticipate that our vaccine used as a fourth dose boost will augment nAb responses in humans. While hamsters also responded to a prime-boost regimen with our RBD vaccines, the response was more varied and not as robust as was observed in mice and rats, which may reflect findings in a recent report of limitations in the extent to which hamsters respond to RBD-based vaccines 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other RBD-targeted neutralizing monoclonal antibodies are unaffected by mutations in the RBD of emerging variants ( Dejnirattisai et al, 2021b ; Cerutti et al, 2021 ; Cameroni et al, 2022 ). Moreover, the utilization of RBD as an immunogen in several vaccine platforms has shown promising clinical immunogenicity results ( Mulligan et al, 2020 ; Yang et al, 2021 ; Janssen et al, 2022 ; Chen et al, 2022 ). Thus, rationally engineered SARS-CoV-2 RBD and spike proteins could serve as potential immunogens to elicit potent protective immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Promisingly, neutralization efficacy of multiple identified RBD-targeted neutralizing monoclonal antibodies is unaffected by mutations in the RBD of emerging variants [10][11][12] . Moreover, the utilization of RBD as an immunogen in several vaccine platforms has shown promising clinical immunogenicity results [13][14][15][16] . Thus, rationally engineered SARS-CoV-2 RBD and spike proteins could serve as potential immunogens to elicit potent protective immune responses.…”
Section: Introductionmentioning
confidence: 99%